The Research Progress of Antiangiogenic Therapy, Immune Therapy and Tumor Microenvironment - Hu, Haoyue; Chen, Yue; Tan, Songtao; Wu, Silin; Huang, Yan; Fu, Shengya; Luo, Feng; He, Jun (Frontiers in Immunology, 2022)
Anti-angiogenesis therapy, a promising strategy against cancer progression, is limited by drug-resistance, which could be attributed to changes within the tumor microenvironment. Studies have increasingly shown that combining anti-angiogenesis drugs with immunotherapy synergistically inhibits tumor growth and progression. Combination of anti-angiogenesis therapy and immunotherapy are well-established therapeutic options among solid tumors, such as non-small cell lung cancer, hepatic cell carcinoma, and renal cell carcinoma. However, this combination has achieved an unsatisfactory effect among some tumors, such as breast cancer, glioblastoma, and pancreatic ductal adenocarcinoma. Therefore, resistance to anti-angiogenesis agents, as well as a lack of biomarkers, remains a challenge. In this review, the current anti-angiogenesis therapies and corresponding drug-resistance, the relationship between tumor microenvironment and immunotherapy, and the latest progress on the combination of both therapeutic modalities are discussed. The aim of this review is to discuss whether the combination of anti-angiogenesis therapy and immunotherapy can exert synergistic antitumor effects, which can provide a basis to exploring new targets and developing more advanced strategies.